O COORDENADOR PEDAGÓGICO E A FORMAÇÃO CONTINUADA DOS PROFISSIONAIS DE CRECHE: POSSIBILIDADES E DESAFIOS - Moyano, Jozina Alves (2014)
The National Education Plan (PNE) states that 50pcenter of children aged 0 to 3 years have guaranteed jobs and Crèches in Public Law No Floor. 11.738/08 presents, in its fourth paragraph, that the composition of the working day of a third teacher for the training shall be observed-. The determination of these changes increases the concern and responsibility in qualifying continuing education in these institutions, which still feel the weight of years of neglect. For actuality and thematic importance, this approach investigates the formative and professional career educators Crèche, with the goal of enabling reflection and analysis of the strategies used in continuing education, as well as a dialectical debate between the practices and theories brought in studies and research. Through the methodology of Field Research Qualitative Nature was sought, contact the professionals at five nurseries in Sao Bernardo do Campo, investigate the following question: How the Education Coordinator who works in childcare has helped or not with the formation of reflective practitioners, researchers and authors of their own practice? In order to answer the question, we carried out interviews with five Pedagogical Coordinators (PCs), three teachers and two assistants in Education and in view of higher subsidies needed to debate, were also interviewed a Coordinating a pedagogy course, with the order to broaden the knowledge of the pedagogy course today, and Management (Head of Region) of Sao Bernardo do Campo, in order to understand the look that the municipality has today for the nursery. Importantly, the focus of the interviews was the work of the CP and the investigative work with other professionals involved in help seeking and obtaining answers to the questions that led to the construction of this work. The theoretical framework developed through the methodology of the Survey of Nature Bibliographical and Documentary for review of the available literature on the subject, are anchored in Placco and Almeida (2002, 2010, 2011) observe that the role of CP in several respects; Day (1999) that discusses the key challenges to be considered in the formation; Fullan and Hargreaves (2002) who have questions about the training strategies; Nóvoa (2009) to investigate the ongoing training of teachers; Thurler and Perrenoud (2002) highlighting new paradigms in teacher training; Vasconcellos (2009) observes that the necessary work of CP joints; Campos et al (2011) show that the quality of early childhood education in the country, among others. The content analysis of the interviews indicates that continued training progresses gradually, and this merit is given, in large part, to the training that managers have been receiving and productive partnerships that are established in the process, however, studies and theoretical studies show that much remains to be done and signal fundamental changes and are able to boost the training out of traditionalism, becoming more focused on reflection and humanization.